PENGGUNAAN GLUTAMIN PADA PAKAN KOMERSIL UNTUK PERTUMBUHAN DAN KELANGSUNGAN HIDUP LOBSTER AIR TAWAR (C. quadricarinatus) - Nurvanni; Abdul Samad, Agus Putra; Komariyah, Siti; Hasri, Iwan (University of Prof. Dr. Hazairin, SH, 2024)
Freshwater lobster (C. quadricarinatus) is a commodity that lives in lakes, swamps, and rivers. Currently, freshwater lobsters are in great demand both for consumption and for aquarium aesthetics. This research is to increase the growth and survival of freshwater crayfish by using the method of different doses of glutamine in commercial feed. The research design carried out was a Completely Randomized Design (CRD). consisting of 4 treatments with 3 repetitions. During the 35 day rearing period, research showed significant differences between each treatment in absolute weight growth, absolute length, weight growth percentage, daily growth rate, and survival of Freshwater Lobster (C. quadricarinatus). The use of glutamine in commercial feed shows that the best results in glutamine dosage for the growth of Freshwater Lobster (C.quadricarinatus) were found in the V2 treatment with a dose of 2% ml and the lowest in the control V0 treatment. This study recommends the use of glutamine in commercial feed to increase the growth and survival of freshwater lobsters (C. quadricarinatus)